Evaluacija zdravlja zuba kod adolescenata sa mentalnim poremećajima - Djordjević, Vladan; Jovanović, Mila; Čolić, Sanja; Stašević, Milena; Asotić, Amina; Čakić, Saša; Stašević Karličić, Ivana; Todorović, Ljubomir (Vojnosanitetski pregled, 2021)
Background/Aim. According to the World Health Organization (WHO), there is an increasing prevalence of mental disorders among children and adolescents worldwide. Previous studies have shown that people with mental disorders, regardless age, have an increased prevalence of dental caries due to several reasons. The aim of this study was to determine prevalence of dental caries in adolescents with mental disorders and to consider possible risk factors that might contribute to their current dental health status. Methods. The study was conducted as an observational cross-sectional study. The study group comprised 70 randomly selected hospitalized adolescents with mental disorders. The control group comprised 70 randomly chosen mentally healthy adolescents. They were matched to the study group by gender and age. All the participants were subjected to targeted dental examination according to criteria recommended by the WHO. Collection of data related to mental disorders of the study group was obtained from the patient’s medical records. All collected data were organized and analyzed by descriptive statistical parameters and regression models. Results. Majority of the study group patients were diagnosed with schizophrenia, schizotypal and delusional disorders (F20-F29), as well as behavioral and emotional disorders usually occurring in childhood and adolescence (F90-F98). Almost 90% of them were treated with antipsychotics of the second generation, as monotherapy or in combination with first-generation antipsychotics. Adolescents with mental disorders had significantly more carious and extracted teeth and three times less filled teeth than mentally healthy adolescents in the control group. The mean value of the decay-missing-filled teeth (DMF) index in the study group patients was also significantly higher than the mean value of DMF index in the control group subjects. Conclusion. It seems that mental disorder among adolescents mainly affects oral health indirectly, decreasing motivation of patients in maintaining oral hygiene.